Hypothyroidism In Women With Recurrent Spontaneous Abortion - EMARAH, MOHAMED S. A.; EL-NAGGAR, MOHAMED A.; SHABACY, ABEER EL; QUSHWA, SAHAR H. (Advances in Social Sciences Research Journal, 2020)
Recurrent miscarriage, defined as loss of two or more consecutive pregnancies, occurs in 1–2% of couples attempting to bear children. The major causes of recurrent pregnancy loss (RPL) based on the literature include parental structural chromosome rearrangement, immunologic factors (i.e. antiphospholipid syndrome), thrombophilic factors (both inherited and acquired), anatomic factors of uterine anomalies, and endocrinologic disorders. Luteal phase defect, polycystic ovarian syndrome (PCOS), diabetes mellitus, thyroid disease and hyperprolactinemia are among the endocrinologic disorders implicated in approximately 17% to 20% of RPL. The prevalence of hypothyroidism in the general population of reproductive age is about 2-3%. The aim of this study is to observe the benefit of screening for hypothyroidism amongst women with recurrent spontaneous abortion early in the first trimester. The study included one hundred and sixty (160) women, in the reproductive age of life, where there ages ranged from 20 – 33 years, and divided into two groups. Study group which included eighty (80), non pregnant women with a history of two or more consecutive spontaneous abortions early in the first trimester, with no living children and control group which included eighty (80), non pregnant women having one or more living children without any history of abortion. Hypothyroidism was noted in ten (10) cases (12.5%) in the study group and noted in two (2) cases (2.5%) in the control group with a statistically significant difference (P < 0.01). The mean levels of TSH in the study group was 22.71  13.13 Iu/ml. Conclusion: Screening for hypothyroidism has clinical significance and would help to reduce miscarriage rate in women with recurrent spontaneous abortion.